CLAIM, DATA AND WARRANT USED IN JUSTIN TRUDEAU’S SPEECHES - Nurfia Maliza; Tria Novita Br Karo Sekali; Dharmadiah Dharmadiah; Rifky Sultan Nico; Diana Sopha (Fakultas Sastra UMN AL Washliyah, 2023)
This study aims to determine the elements of argumentative writing in the form of claims, data and warrants in 5 speeches by Canadian President Justin Trudeau entitled